DEVELOPMENT OF SELF-ASSESSMENT IN PEDAGOGICAL ACTIVITY THROUGH REFLECTION - Avulova Fotima; Salixova Muxayyo (Bright Mind Publishing, 2026)
This article deals with the development of self-assessment in pedagogical activity through reflection. The study reveals the importance of the reflexive approach in the educational process and analyzes the possibilities of improving the professional activities of teachers based on the theories of scientists such as John Dewey, Donald Schont, Graham Gibbs. The article substantiates that reflection is an important factor in the formation of critical thinking and professional development in teachers.
Keywords: Reflexion, pedagogical skills, professional skills, personal reflexion, professional reflexion, social reflexion, professional development.